Wireless communications principles and practice - Rappaport, Theodore S. (Prentice Hall, 1996)
As cellular telephones become commonplace business tools, interest in wireless technology is booming. This book responds to that demand with a comprehensive survey of the field, suitable for educational or technical use. Materials are drawn from academic and business sources, numerous journals, and an IEEE professional reader. Extensively illustrated, Wireless Communications is filled with examples and problems, solved step by step and clearly explained.Wireless Communications covers the design fundamentals of cellular systems, including issues of frequency reuse, channel assignments, radio propagation, and both analog and digital modulation techniques. Speech coding, channel coding, diversity, spread spectrum, and multiple access are also discussed. A separate chapter is devoted to wireless networking, including SS7 and ISDN.Beyond theory,Wireless Communications offers practical reference sections, including: * Complete technical standards for cellular, cordless telephone, and personal communications systems * International standards for Europe, the Americas, and the Asia-Pacific region * Noise figure calculations and Gaussian approximations of spread spectrum CDMA interference * Mathematical tables, identities, and the Q, erf, and erf functions * Glossary of abbreviations and acronyms * Full list of references This book is designed for use in graduate and undergraduate classrooms, but is also suitable for use by professional engineers and technicians. It can be used for both teaching and reference, and is also appropriate for the interested cellular phone consumer who wants to understand the technology.